Shame is Already a Revolution: The Politics of Affect in the Thought of Gilles Deleuze. Issue 1 (February 2017) - O'Donnell, Aislinn
Abstract : The concept of shame is important for Deleuze's ethics and politics. In this essay, shame is positioned within a nexus of concepts: the intolerable, seeing, resistance, powerlessness, and belief in this world. If one has fallen short, it is not because of who one is, how one is seen, or how one has been judged, but it is, in part, because of one's failure to see what is intolerable. In this respect, shame, in particular 'the shame of the world', has the potential to be a proto-political and proto-ethical affect because it suspends and precludes the ready invocation of clichés and explanations that buttress us against reality. This disruption in turn opens a space for creativity and resistance.